Explosive Signature of The April 30th, 2024 Ruang Volcano Eruption in The Sangihe Arc, Indonesia, Inferred from Erupted Material Characteristics: A Preliminary Assessment - Purnamasari, Heruningtyas Desi; Saepuloh, Asep; Primulyana, Sofyan; Adriansyah, David; Prayoga, Ardy Setya; Agustiningtyas, Lestari; Wijaya, P. Hadi; Gunawan, Hendra (Indonesian Journal on Geoscience, 2025)
The 2024 eruptions of Ruang Volcano in North Sulawesi, Indonesia, represent one of the most explosive and impactful volcanic events in the region's recent history. The eruption sequence, which commenced on April 16th and peaked with significant explosive episodes on April 17th and 30th, resulted in the evacuation of over 9,000 residents and demonstrated the volcano’s capacity for high-energy eruptive activity. This preliminary analysis of the April 30, 2024, Ruang Volcano eruption emphasises the importance of ejected materials—such as high-vesicular juvenile fragments, crystal-rich components, and megacrysts of amphibole (hornblende)—in revealing the eruption’s explosive signature. Geochemical analysis of juvenile materials indicates a basaltic andesite composition, with SiO₂ contents ranging from 53.02% to 54.27%. Petrographic examination and SEM observations reveal high vesicularity, ruptured bubble walls, and microlite-rich groundmass textures, indicative of rapid ascent and intense degassing, which facilitated efficient magma fragmentation. These features suggest that the magma underwent rapid decompression. Understanding these properties provides important clues about the mechanisms underlying the explosiveness of the Ruang eruption.